Legal Changes in Tax Penalties Applied to Enterprises in Vietnam in the International Integration - Giang, Nguyễn Thúc Hương (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2015)
Abstract: In the international integration, economic changes have had a strong influence on domestic and foreign enterprises inVietnam regarding tax compliance. The more domestic and international activities occur, the more the enterprises have to take advantage of tax evasion and tax avoidance. By using historical methodologies, this paper tries to point out the shortcomings of the current regulations on tax penalties applied to enterprises inVietnam and proposes orientation solutions. The research shows that as administrative sanctions change for international integration, criminal penalties therefore also change but not sufficiently. There is no distinction between criminal sanctions for taxpayers as individuals or as businesses. Tax law violations are sometimes the consequences ofVietnam’s economic integration, but yet to be specified. Otherwise, many regulations can not be executed because of conflict, or tax departments do not have enough capacity or conditions to implement the regulations. Solutions to further revise and complete the tax legislation on administrative and criminal penalties applied to enterprises inVietnam are proposed in this article. Keywords: Tax penalties, tax evasion, tax avoidance, tax control, economic integration.